Capability of contrast enhanced magnetic resonance tomography in accurate grading of chondrosarcoma - A. V. Fedorova; N. V. Kochergina; I. V. Boulytcheva; E. A. Sushentsov; A. S. Nered; Y. A. Shchipakhina; A. B. Bludov (Бюллетень сибирской медицины)
Chondrosarcoma is one of the most common tumors in adults. Correct grading of chondrosarcoma is the most important criterion that defines the course of surgical treatment. A case report of a 56 years old female patient with chondrosarcoma of the pelvic bone is presented. The assistance of magnetic resonance tomography in accurate grading of the tumor is shown.